A solid electrolyte and its preparation method and application

By introducing cosolvents into the solid electrolyte, combining polymer electrolyte, lithium salt and sulfide solid electrolyte, the problem of poor rate performance of solid electrolyte in low temperature environments is solved, and higher thermal stability and discharge capacity are achieved.

CN119742426APending Publication Date: 2025-04-01SICHUAN CHANGHONG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411940299.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing solid electrolytes have poor performance in rate at room temperature or lower temperatures, and polymer electrolytes can only operate at high temperatures, which limits their application scenarios.

Method used

A solid electrolyte consisting of polymer electrolyte, lithium salt, cosolvent, additive and sulfide solid electrolyte is adopted, and cosolvent is introduced through specific compositional proportions and preparation methods to improve the thermal stability and ionic conductivity of the electrolyte.

Benefits of technology

It realizes better thermal stability of solid electrolyte at high temperatures, and improves the discharge capacity and rate performance of the battery at low temperatures and room temperatures, solving the problem of insufficient performance of solid electrolyte in the low temperature environment in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212438550000052
    Figure BDA0005212438550000052
  • Figure BDA0005212438550000062
    Figure BDA0005212438550000062
  • Figure BDA0005212438550000072
    Figure BDA0005212438550000072
Patent Text Reader

Abstract

The present invention discloses a solid electrolyte and a preparation method and application thereof. The solid electrolyte in the present invention comprises a polymer electrolyte, a lithium salt, a cosolvent, an additive and a sulfide solid electrolyte; wherein the cosolvent comprises a substance A and a substance B. The present invention introduces a cosolvent composed of substances A and B, so that the solid electrolyte prepared by the present invention has better thermal stability at high temperatures, and the battery assembled by the electrolyte also has more discharge capacity at low temperatures (-40°C) and room temperatures (25°C), thereby solving the problem of poor rate performance of solid electrolytes in the prior art at room temperatures or lower temperatures, and breaking the limitation that polymer electrolytes can only operate at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] High-safety, high-energy-density, and low-cost lithium-ion batteries are the development trend of the industry. Therefore, most researchers believe that the development of high-safety, high-energy-density solid-state batteries is an inevitable choice. Among them, the research on solid-state electrolytes is an important direction for solid-state batteries. At present, solid-state electrolytes are mainly divided into three categories, namely oxide solid-state electrolytes, polymer solid-state electrolytes, and sulfide solid-state electrolytes. Each has its own advantages and disadvantages. Independent use cannot meet the needs of commercial battery use. Therefore, researchers usually combine their respective advantages to prepare composite electrolytes. In order to further improve the wide temperature performance of composite electrolytes, various solvents, additives, inorganic fillers, etc. are usually introduced. For example, in the article "Patent No.: CN202310382079.8, Patent Name: A Method for Preparing a Composite Solid-State Electrolyte", a composite electrolyte is formed by adding a fast ion conductor at the same time. However, since the fast ion conductor electrolyte is an inorganic substance and the polymer electrolyte is an organic substance, the two are mixed, and the fast ion conductor is prone to sedimentation, resulting in uneven electrolyte mixing, large differences in battery consistency, and difficulty in scaling up the process. The article "Patent Number: CN202110717915.4, Patent Name: Preparation of a Sulfonic Acid Polymer Eutectic Solid Electrolyte" reduces the dissociation transition energy barrier of lithium ions by adding amide groups and sulfonic acid groups with complexing and coordination capabilities, thereby improving battery performance; however, the disadvantage of polymer electrolytes is that they have low ionic conductivity and can only operate at high temperatures, and their application scenarios are relatively limited.

[0003] From the above, it can be seen that although solid-state electrolytes have received widespread attention in the industry due to their advantages such as high safety and high energy density, solid-state electrolytes have poor rate performance at room temperature or lower temperatures, resulting in the inability of positive and negative electrode materials to perform effectively; and polymer electrolytes can only operate at high temperatures. Summary of the invention

[0004] In order to solve the problem that existing solid electrolytes have poor performance at room temperature or lower temperatures, one of the purposes of the present invention is to provide a solid electrolyte.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a solid electrolyte, including a polymer electrolyte, a lithium salt, a co-solvent, an additive and a sulfide solid electrolyte;

[0006] The co-solvent includes substance A and substance B;

[0007] The general structural formula of substance A is: Among them, R 1 , R 2is any one of hydrogen, a halogen atom and a methyl group;

[0008] The general structural formula of substance B is: Among them, R 3 , R 4 , R 5 It is any one of hydrogen, a halogen atom and an alkyl group having 1 to 5 carbon atoms.

[0009] On the basis of the above technical solution, the present invention can also be improved as follows:

[0010] Furthermore, the polymer electrolyte is polyethylene oxide and / or polyvinylidene fluoride.

[0011] Furthermore, the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium dioxalatoborate and lithium nitrate.

[0012] Furthermore, the additive is at least one of tris(trimethylsilyl)phosphate, triethyl phosphate, succinonitrile and fluoroethylene carbonate.

[0013] Furthermore, the sulfide solid electrolyte is Li 7 P 3 S 11 and / or Li 10 G 2 S 12 .

[0014] Furthermore, the mass fraction of the polymer electrolyte is 32.2% to 39.1%, the mass fraction of the lithium salt is 25.8% to 31.5%, the mass fraction of substance A is 7.8% to 13.6%, the mass fraction of substance B is 11.2% to 20%, the mass fraction of the additive is 1.96% to 3.3%, and the mass fraction of the sulfide solid electrolyte is 6.5% to 16.2%.

[0015] The second object of the present invention is to provide a method for preparing the solid electrolyte in the first object, comprising the following steps:

[0016] Step 1, stirring and dissolving the polymer electrolyte in a mixed solvent, adding a lithium salt and stirring until the lithium salt is dissolved;

[0017] Step 2, add co-solvent and continue stirring;

[0018] Step 3, adding additives and sulfide solid electrolyte in sequence and continuing stirring to obtain a solid electrolyte precursor;

[0019] Step 4: coating a solid electrolyte precursor on the diaphragm and drying to obtain a solid electrolyte.

[0020] Furthermore, the mixed solvent includes tetrahydrofuran and N,N-dimethylformamide in a mass ratio of 1:1.

[0021] Further, the stirring temperature in step 1, step 2 and step 3 is 40°C to 50°C, the stirring time of the polymer electrolyte dissolved in the mixed solvent in step 1 is 2h to 4h, the stirring time of the lithium salt dissolved is 2h to 4h, the stirring time in step 2 is 1h to 2h, and the stirring time in step 3 is 1h to 2h;

[0022] The drying conditions in step 4 are: vacuum, drying temperature 70° C. to 90° C., and drying time 8 h to 10 h.

[0023] The third object of the present invention is to provide a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, and a solid electrolyte located on the separator and as described in the first object or the solid electrolyte prepared in the second object.

[0024] The present invention has the following beneficial effects:

[0025] 1. The present invention introduces a co-solvent composed of substance A and substance B. According to subsequent test analysis, the solid electrolyte prepared by the present invention has better thermal stability at high temperatures, and the battery assembled by the electrolyte also has more discharge capacity at low temperature (-40°C) and room temperature (25°C), which solves the problem of poor rate performance of solid electrolytes in the prior art at room temperature or lower temperatures, and breaks the limitation that polymer electrolytes can only operate at high temperatures.

[0026] 2. In the present invention, aromatic solvents and fluorinated nitrile substances are selected to form a co-solvent, and the co-solvent formed is conducive to the formation of an inorganic SEI film, improving the ionic conductivity, and improving the battery rate performance while also improving the wide temperature stability of the battery. The reason is that substance A in the present invention has intramolecular hydrogen bonds. After substance A and substance B are mixed, the intramolecular hydrogen bonds of substance A will be destroyed, and intermolecular hydrogen bonds will be formed between the two, thereby reducing the viscosity of the mixed solution and widening the physicochemical properties of the mixed solution (especially the melting point of the substance), which is conducive to improving the ionic conductivity of the electrolyte; in addition, the introduction of aromatic groups and fluorinated nitrile groups into the structures of substances A and B is conducive to the formation of an inorganic SEI film during the electrochemical cycle, which can further improve battery performance.

[0027] 3. The substance A in the present invention contains an amide bond, which can react with the residual NMP (N-methylpyrrolidone) solvent in the positive electrode sheet (when the positive electrode sheet is normally prepared, a small amount of NMP will remain in the positive electrode sheet) to form a complex, thereby reducing the presence of free NMP and improving the battery cycle performance; and it can also form a hydrogen bond force with the negative electrode binder (such as sodium carboxymethyl cellulose, polyacrylic acid, etc.), thereby improving the interface stability and thus improving the battery performance.

[0028] In addition, since substance A contains an amide bond, it is essentially an amide substance, and the sulfur ions in the sulfide will form a strong hydrogen bond with the NH in the amide bond, and the lithium ions will form a coordination with the C=O in the acyl group, thereby dissolving the sulfide solid electrolyte; and when it is used in combination with an ether electrolyte, the ether electrolyte plays a solvating role in dissolving the sulfide electrolyte, thereby improving the solubility of the sulfide solid electrolyte, promoting the dissolution of the sulfide solid electrolyte, improving the uniformity of the composite electrolyte, and ensuring the consistency of battery performance. DETAILED DESCRIPTION

[0029] A solid electrolyte, a preparation method and an application thereof in the present application will be described below in conjunction with embodiments.

[0030] However, the present application may be exemplified in many different forms and should not be construed as limited to the specific embodiments set forth herein. Rather, these embodiments are provided so that the present application will be thorough and complete and will fully convey the scope of the present application to those skilled in the art.

[0031] Example 1

[0032] A method for preparing a solid electrolyte comprises the following steps:

[0033] Step 1, weigh 39.1% PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 25.39% lithium bistrifluoromethylsulfonyl imide and 5.86% lithium bis(oxalatoborate) by mass, and continue stirring at 40°C for 4h.

[0034] Step 2: Add 7.8% by mass of substance A and 11.72% by mass of substance B in sequence, and stir at 40°C for 1 hour. The structure of substance A is: The structure of substance B is:

[0035] Step 3: Then, 0.78% tris(trimethylsilyl)phosphate, 1.54% succinonitrile and 7.81% Li 7 P 3 S 11 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0036] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0037] The solid electrolyte-loaded separator is composed of a ternary positive electrode, a silicon-carbon negative electrode, and an electrolyte (1M LiTFSI dissolved in DOL:DME:EC=4:5:1 (the volume ratio of chlorocycloalkane to ethylene glycol dimethyl ether and ethylene carbonate is 4:5:1)) and assembled into a 2.5Ah / 18650 cylindrical battery.

[0038] Example 2

[0039] A method for preparing a solid electrolyte comprises the following steps:

[0040] Step 1, weigh 25.80% PVDF and 6.40% PEO (polyethylene glycol) by mass, dissolve them in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 20.97% lithium bistrifluoromethylsulfonyl imide and 4.83% lithium bis(oxalatoborate) by mass, and continue stirring at 40°C for 4h.

[0041] Step 2: Add 9.60% by mass of substance A and 12.90% by mass of substance B in sequence, and stir at 40°C for 1 hour. The structure of substance A is: The structure of substance B is:

[0042] Step 3: Then, 0.66% of triethyl phosphate, 1.32% of succinonitrile, 1.32% of fluoroethylene carbonate and 16.20% of Li were added in sequence. 7 P 3 S 11 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0043] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0044] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0045] Example 3

[0046] A method for preparing a solid electrolyte comprises the following steps:

[0047] Step 1, weigh 32.68% of PVDF and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 21.24% of lithium bistrifluoromethylsulfonyl imide and 4.90% of lithium bis(oxalatoborate), and continue stirring at 40°C for 4h;

[0048] Step 2: Add 12.72% of substance A and 20% of substance B in sequence, and stir at 40°C for 1 hour. The structure of substance A is: The structure of substance B is:

[0049] Step 3: Then, 0.65% tris(trimethylsilyl)phosphate, 1.31% succinonitrile and 6.5% Li 7 P 3 S 11 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0050] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0051] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0052] Example 4

[0053] A method for preparing a solid electrolyte comprises the following steps:

[0054] Step 1, weigh 36.23% of PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 50°C for 2h; then add 23.55% of lithium bistrifluoromethylsulfonyl imide and 5.43% of lithium bis(oxalatoborate) and continue stirring at 50°C for 4h.

[0055] Step 2: Add 10.87% by mass of substance A and 14.49% by mass of substance B in sequence, and stir at 50°C for 1 hour. The structure of substance A is: The structure of substance B is:

[0056] Step 3: Then, 0.72% by mass of fluoroethylene carbonate, 1.45% by mass of succinonitrile and 7.26% by mass of Li were added in sequence. 7 P 3 S 11 , continue stirring for 1 h to obtain a solid electrolyte precursor;

[0057] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0058] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0059] Example 5

[0060] A method for preparing a solid electrolyte comprises the following steps:

[0061] Step 1, weigh 33.78% of PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 21.96% of lithium bistrifluoromethylsulfonyl imide and 5.07% of lithium bis(oxalatoborate), and continue stirring at 40°C for 4h.

[0062] Step 2: Add 13.6% by mass of substance A and 16.8% by mass of substance B in sequence, and stir at 40°C for 1 hour. The structure of substance A is: The structure of substance B is:

[0063] Step 3: Then, 0.68% of triethyl phosphate, 1.35% of succinonitrile and 6.76% of Li 7 P 3 S 11 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0064] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it at 90° C. in vacuum for 8 h to obtain a solid electrolyte.

[0065] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0066] Example 6

[0067] A method for preparing a solid electrolyte comprises the following steps:

[0068] Step 1, weigh 37.59% PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 4h; then add 24.44% lithium bistrifluoromethylsulfonyl imide and 5.64% lithium bis(oxalatoborate) by mass, and continue stirring at 50°C for 2h.

[0069] Step 2: Add 11.28% of substance A and 11.28% of substance B in sequence, and stir at 40°C for 2h. The structure of substance A is: The structure of substance B is:

[0070] Step 3: Then, 0.75% tris(trimethylsilyl)phosphate, 1.5% succinonitrile and 7.52% Li 10 G 2 S 12 , and continue stirring for 2 h to obtain a solid electrolyte precursor.

[0071] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it at 70° C. in vacuum for 10 h to obtain a solid electrolyte.

[0072] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0073] Example 7

[0074] A method for preparing a solid electrolyte comprises the following steps:

[0075] Step 1, weigh 39.06% of PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 25.54% of lithium bistrifluoromethylsulfonyl imide and 5.96% of lithium bis(oxalatoborate) and continue stirring at 40°C for 4h.

[0076] Step 2: Add 7.81% of substance A and 11.2% of substance B in sequence, and stir at 40°C for 1 hour. The structure of substance A is: The structure of substance B is

[0077] Step 3: Then, 0.78% tris(trimethylsilyl)phosphate, 1.56% succinonitrile and 8.09% Li 10 G 2 S 12 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0078] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0079] The solid electrolyte-loaded diaphragm is assembled with the ternary positive electrode, the silicon-carbon negative electrode, and the electrolyte (1M LiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0080] Comparative Example 1

[0081] A method for preparing a solid electrolyte comprises the following steps:

[0082] Step 1, weigh 48.55% of PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 31.55% of lithium bistrifluoromethylsulfonyl imide and 7.28% of lithium bis(oxalatoborate), and continue stirring at 40°C for 4h.

[0083] Step 2: Then, 0.97% tris(trimethylsilyl)phosphate, 1.94% succinonitrile and 9.71% Li 7 P 3 S 11 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0084] Step 3: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0085] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0086] Comparative Example 2

[0087] A method for preparing a solid electrolyte comprises the following steps:

[0088] Step 1, weigh 44.24% of PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 28.76% of lithium bistrifluoromethylsulfonyl imide and 6.64% of lithium bis(oxalatoborate), and continue stirring at 40°C for 4h.

[0089] Step 2, add 8.85% of substance A and stir at 40°C for 1h; wherein the structure of A is:

[0090] Step 3: Then, 0.89% tris(trimethylsilyl)phosphate, 1.77% succinonitrile and 8.85% Li 7 P 3 S 11 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0091] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0092] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0093] Comparative Example 3

[0094] A method for preparing a solid electrolyte comprises the following steps:

[0095] Step 1, weigh 42.38% of PVDF (polyvinylidene fluoride) and dissolve it in 20g of a mixed solvent consisting of tetrahydrofuran and N,N-dimethylformamide (wherein the mass ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1), and stir at 40°C for 2h; then add 27.54% of lithium bistrifluoromethylsulfonyl imide and 6.36% of lithium bis(oxalatoborate), and continue stirring at 40°C for 4h.

[0096] Step 2: Add 12.71% of substance B by mass and stir at 40°C for 1 hour. The structure of substance B is:

[0097] Step 3: Then, 0.85% tris(trimethylsilyl)phosphate, 1.69% succinonitrile and 8.47% Li 7 P 3 S 11 , and continue stirring for 1 h to obtain a solid electrolyte precursor.

[0098] Step 4: evenly coat the solid electrolyte precursor on the surface of the diaphragm and dry it under vacuum at 80° C. for 9 h to obtain a solid electrolyte.

[0099] The diaphragm loaded with solid electrolyte is assembled with the ternary positive electrode, silicon-carbon negative electrode, and electrolyte (1MLiTFSI dissolved in DOL:DME:EC=4:5:1 (volume ratio)) to form a 2.5Ah / 18650 cylindrical battery.

[0100] Test analysis:

[0101] 1. The solid electrolytes prepared in the above examples and comparative examples were baked at 150° C. for 1 h, and the morphological changes of the solid electrolytes were observed. The results are shown in Table 1.

[0102] Table 1. Results of high temperature baking of solid electrolyte

[0103]

[0104]

[0105] It can be seen from Table 1 that the solid electrolyte prepared in the present invention has almost no shrinkage and deformation, that is, the surface solid electrolyte coating prepared in the present invention can effectively improve the thermal stability of the electrolyte membrane and ultimately improve the safety performance of the battery.

[0106] 2. After the pre-charging of the batteries assembled in the above embodiments and comparative examples, their performances were tested. The test results are shown in Table 2.

[0107] Table 2. Battery performance test results

[0108]

[0109]

[0110] It can be seen from Table 2 that, compared with Comparative Examples 1 to 3, the battery assembled by introducing a solid electrolyte prepared by introducing a co-solvent in the present invention has a higher discharge capacity at low temperature and room temperature, and a greater discharge capacity at a high rate of 30A, and a longer cycle life, and the wide temperature performance, rate performance, and cycle life of the battery are effectively improved.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid electrolyte, characterized in that Including polymer electrolytes, lithium salts, co-solvents, additives and sulfide solid electrolytes; The co-solvent includes substance A and substance B; The general structural formula of the substance A is: Wherein, R1 and R2 are any one of hydrogen, halogen atom and methyl; The general structural formula of the substance B is: Wherein, R3, R4, and R5 are any one of hydrogen, a halogen atom, and an alkyl group having 1 to 5 carbon atoms.

2. The solid electrolyte according to claim 1, characterized in that The polymer electrolyte is polyethylene oxide and / or polyvinylidene fluoride.

3. The solid electrolyte according to claim 2, characterized in that The lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium dioxalatoborate and lithium nitrate.

4. The solid electrolyte according to claim 3, characterized in that The additive is at least one of tris(trimethylsilyl)phosphate, triethyl phosphate, succinonitrile and fluoroethylene carbonate.

5. The solid electrolyte according to claim 4, characterized in that The sulfide solid electrolyte is Li7P3S 11 and / or Li 10 GeP2S 12 .

6. The solid electrolyte according to any one of claims 1 to 5, characterized in that: The mass fraction of the polymer electrolyte is 32.2% to 39.1%, the mass fraction of the lithium salt is 25.8% to 31.5%, the mass fraction of substance A is 7.8% to 13.6%, the mass fraction of substance B is 11.2% to 20%, the mass fraction of the additive is 1.96% to 3.3%, and the mass fraction of the sulfide solid electrolyte is 6.5% to 16.2%.

7. The method for preparing the solid electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, stirring and dissolving the polymer electrolyte in a mixed solvent, adding a lithium salt and stirring until the lithium salt is dissolved; Step 2, add co-solvent and continue stirring; Step 3, adding additives and sulfide solid electrolyte in sequence and continuing stirring to obtain a solid electrolyte precursor; Step 4: coating a solid electrolyte precursor on the diaphragm and drying to obtain a solid electrolyte.

8. The preparation method according to claim 7, characterized in that: The mixed solvent includes tetrahydrofuran and N,N-dimethylformamide in a mass ratio of 1:

1.

9. The preparation method according to claim 7, characterized in that: The stirring temperature in step 1, step 2 and step 3 is 40°C to 50°C, the stirring time of the polymer electrolyte dissolved in the mixed solvent in step 1 is 2h to 4h, the stirring time of the lithium salt dissolved is 2h to 4h, the stirring time in step 2 is 1h to 2h, and the stirring time in step 3 is 1h to 2h; The drying conditions in step 4 are: vacuum, drying temperature 70° C. to 90° C., and drying time 8 h to 10 h.

10. A solid-state battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a diaphragm and a solid electrolyte as claimed in any one of claims 1 to 6 or a solid electrolyte prepared by the method as claimed in any one of claims 7 to 9 located on the diaphragm.

Citation Information

Patent Citations

  • A sulfonic acid-based polymer eutectic solid electrolyte and its preparation method

    CN113363575B

  • Composite solid electrolyte, preparation method thereof and lithium metal battery

    CN116454370A